Controlling strategiczny a modele organizacji doradztwa strategicznego - Bieńkowska, Agnieszka; Kral, Zygmunt; Zabłocka-Kluczka, Anna (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
Topicality of a problem of selection a proper concept of strategic controlling in a context of model of strategic counsel organization was justified. The concepts of strategic controlling understood as information supporting management, coordination of management and a special form of management were presented. Models of strategic counsel organization were listed and characterized. Four following models were taken into considerations: wholly deconcentrated, deconcentrated with a prevailing role of one from organizational cells, concentrated with a temporary personal frame and concentrated with a constant personal frame. The concepts of strategic controlling were combined with the models of strategic counsel organization. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1080, s. 31-43